Sexy Like Us : Disability, Humor, and Sexuality - Milbrodt, Teresa, 1978- (Book collections on Project MUSE., 2022)
"Sexy Like Us: Disability, Humor, and Sexuality takes a humorous, intimate approach to disability through the stories, jokes, performances, and other creative expressions of people with disabilities. Author Teresa Milbrodt explores why individuals can laugh at their leglessness, find stoma bags sexual, discover intimacy in scars, and flaunt their fragility in ways both hilarious and serious. Their creative and comic acts crash, collide, and collaborate with perceptions of disability in literature and dominant culture, allowing people with disabilities to shape political disability identity and disability pride, call attention to social inequalities, and poke back at ableist cultural norms. This book also discusses how the ambivalent nature of comedy has led to debates within disability communities about when it is acceptable to joke, who has permission to joke, and which jokes should be used inside and outside a community's inner circle. Joking may be difficult when considering aspects of disability that involve physical or emotional pain and struggles to adapt to new forms of embodiment. At the same time, people with disabilities can use humor to expand the definitions of disability and sexuality. They can help others with disabilities assert themselves as sexy and sexual. And they can question social norms and stigmas around bodies in ways that open up journeys of being, not just for individuals who consider themselves disabled, but for all people"--